Code-Switching Done by Cinta Laura in “Mang Saswi Jatuh Cinta ke Cinta Laura Ini Talkshow” - I Gusti Ayu Vina Widiadnya Putri; I Gusti Agung Sri Rwa Jayantini; I Dewa Ayu Md A Wahyu Linda Dewi (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
The purpose of this study is to identify the types and reasons for Code-switching in the Youtube channel Ini Talkshow on the program Net TV. This study is concerned with the Codeswitching phenomenon involving the Indonesian-English language that was found in Cinta Laura's speech during channel on the program Net TV. The quantitative and qualitative methods were used in this study. Apple and Muysken's theory (1987:118) is referred to in the study of data to analyze the type of Code-switching, and Hoffman's theory (1991) is referred to analyze the reasons for code-switching. It is done formally and informally to show the product of the analysis. There are found intra-sentential 10 data, inter-sentential 2 data, and tag switching 1 data. The reason for Code-switching are found in talking about a particular topic 25%%, quoting somebody else 10%, showing empathy about something 20%, interjection (inserting sentence fillers or sentence connector) 10%, repetition used for clarification 10%, expressing group identity 10%, and intention of clarifying the speech content for the interlocutor 10%.